2019
DOI: 10.1016/j.plantsci.2018.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Toward the understanding of the role of CDC48, a major component of the protein quality control, in plant immunity

Abstract: The evolutionally conserved chaperone-like protein CDC48 (cell division cycle 48) is a major component of ubiquitin-dependent protein degradation pathways in animal and yeast and, more generally, of the protein quality control machinery. In plants, CDC48 plays essential regulatory functions in development and the possibly that it contributes to protein degradation through the ubiquitin-proteasome system (UPS) and the endoplasmic reticulum-associated protein degradation (ERAD) system has been reported. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 70 publications
(99 reference statements)
2
21
0
Order By: Relevance
“…The proteins with ubiquitin-regulating region X (UBX) participate in Cdc48/p97-substrate binding, as well as in time and space regulation its activity [69]. It probably substantially contributes to plant immunity by precise control of produced proteins in virus-attacked cells [70]. On the other hand, some authors presume positive influence of the ubiquitin-proteasome system on infection by (+)ssRNA viruses by regulation of concentration of particular viral proteins [71].…”
Section: Mock-inoculated Cultivars (Comparison H-/v-)mentioning
confidence: 99%
“…The proteins with ubiquitin-regulating region X (UBX) participate in Cdc48/p97-substrate binding, as well as in time and space regulation its activity [69]. It probably substantially contributes to plant immunity by precise control of produced proteins in virus-attacked cells [70]. On the other hand, some authors presume positive influence of the ubiquitin-proteasome system on infection by (+)ssRNA viruses by regulation of concentration of particular viral proteins [71].…”
Section: Mock-inoculated Cultivars (Comparison H-/v-)mentioning
confidence: 99%
“…AT plants of A10- DS-RFP6 exhibited substantial 16.68-fold increase in CDC48 expression levels in comparison to WT plants. It was reported that the CDC48 could play a crucial regulatory role in plant development besides protein degradation through ubiquitin-proteasome system (UPS) and endoplasmic reticulum-associated protein degradation (ERAD) system (Begue et al ., 2019). Shi et al ., (2019) observed that the transgenic rice overexpressing Os CDC48 promoted increased tiller number and grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of CDC48 function in plant immunity demonstrated that the tobacco CDC48 isoform rapidly accumulates in its hexameric active structure in tobacco cells exposed to cryptogein (165). A screening for its binding partners allowed to the identification of key regulators of the redox status, including cytosolic ascorbate peroxidase (cAPX) a pivotal enzyme for ROS removal (165,166). In CDC48-overexpressing tobacco cells, the activity of cAPX was impaired, leading to severe decrease in the cell capacity to respond to oxidative stress (167).…”
Section: Modulation Of Immune Signaling Pathways By Post-translationamentioning
confidence: 99%